Polybenzimidazole membranes functionalised with 1-methyl-2-mesitylbenzimidazolium ions via a hexyl linker for use in vanadium flow batteries - Lee, Yona; Kim, Sangwon; Maljusch, Artjom; Conradi, Oliver; Kim, Hyoung-Juhn; Jang, Jong Hyun; Han, Jonghee; Kim, Jihyun; Henkensmeier, Dirk (ELSEVIER SCI LTD, 2019)
1-(6-bromohexyl)-3-methyl-2-(2,4,6-trimethylphenyl)-2H-benzimidazolium bromide was synthesised and grafted onto polybenzimidazole (PBI). The highest obtained degrees of functionalisation were 0.7 and 1.1 ionic groups per repeat unit, corresponding to ion exchange capacities of 1.25 and 1.55 mmol chloride/g. While the latter material had much reduced tensile strength and Young's modulus, the material with a lower degree of functionalisation showed properties similar to PBI and was therefore further investigated. X-ray scattering showed that the functional group reduced the crystallinity. Conductivity was in the range of 2-3 mS cm(-1,) but increased to 23 mS cm(-1) after doping in 2 M sulfuric acid, 2-4 times higher than for doped PBI. Permeability for VO2+ ions was 0.8 x 10(-12) m(2) s(-1). In the vanadium redox flow battery, the grafted PBI showed higher coulomb and voltage efficiency than PBI, and therefore also higher energy efficiency.